Analysis of the genetic diversity of grain legume germplasm resources in China and the development of universal SSR primers. Issue 1 (1st January 2021) - Zhou, Runnan; Yang, Siqi; Zhang, Bo; Qi, Zhaoming; Xin, Dawei; Su, Anyu; Li, Sinan; Cheng, Peng; Bai, Yunqi; Yin, Zhengong; Zhang, Binshuo; Zhao, Yujing; et al.
Abstract: The research objects of this paper are Vigna angularis, Vigna radiata and Phaseolus vulgaris, which are important grain legume resources in China. However, the genetic structure between the three species is not clear. Therefore, this study developed a set of universal gSSR (simple sequence repeat) primers based on the whole-genome sequences of adzuki beans, mung beans and common beans and analysed the genetic diversity of the test resources based on universal gSSR loci. A total of 53, 099 pairs of universal primers were developed, and 43 universal primer pairs were selected for analysis of their test resources. The genetic diversity of the tested common bean germplasm resources was the largest, and the genetic diversity of the tested mung bean germplasm resources was the smallest. Based on the structural analysis and NJ algorithm, the genetic relationships of the test resources were analysed. When Δ K = 3, 3 and 2, the test resources were divided into 3, 3 and 2 subgroups, respectively. The average genetic differentiation coefficient among the three species was 0.24, and the average gene flow value was 0.78. The genetic distances among the three species ranged from 0.27 to 0.90. The genetic distance between the tested adzuki bean germplasm resources and the tested mung bean germplasm resources was the closest, and the genetic distance between the test adzuki bean germplasm resources and the tested common bean germplasm resources was the farthest. This study provides a scientific basis for the rational development, protection and sustainable use of germplasm resources.